Inflammatory response induction as a result of BioGlue adhesive application in cardiac surgery - a review of the literature - Tomasz Furgoł; Remigiusz Antończyk; Michał Miciak; Marcin Jezierzański; Maciej Smreczak; Konrad Gigoń; Oskar Fogiel; Maksymilian Ratajczak (Termedia Publishing House, 2024)
BioGlue is one of the best-known substances used as a tissue adhesive during surgical procedures, especially in cardiac surgery. Inappropriate use of BioGlue can result in inflammation in both the heart and adjacent tissues after its intraoperative application. Inflammation caused by BioGlue in cardiac surgery is a topic that has been discussed by numerous authors in scientific studies, meta-analyses and evaluations of this tissue adhesive. However, there is a lack of collected knowledge on this subject in a single concise article. The purpose of this paper is to review the current medical knowledge on the use of BioGlue in cardiac surgery versus the induction of an inflammatory response. Our paper discusses the details of this problem according to the most recent scientific reports.